Central retinal artery occlusion, an early sign of crizotinib resistance in an alk positive adenocarcinoma of lung: A rare case report. (17th October 2016) - Madabhavi, Irappa; Patel, Apurva; Anand, Asha; Panchal, Harsha; Parikh, Sonia
Abstract: About 4% of non‐small‐cell lung carcinomas involve an EML4‐ALK tyrosine kinase fusion gene and occur almost absolutely in carcinomas arising in non‐smokers. Crizotinib, the first inhibitor of anaplastic lymphoma kinase (ALK), ROS1 and c‐Met receptor kinase, has been used in the treatment of ALK‐positive non‐small cell lung cancer. Side effects of crizotinib mostly consist of grade 1–2 gastrointestinal events (nausea, vomiting, diarrhea and constipation), grade 1–2 edema and fatigue; grade 1 visual disorders, rare cases of elevated liver enzymes and pneumonitis. We are presenting a case of adenocarcinoma of lung, who progressed on first‐line chemotherapy and received crizotinib as second line therapy for 9 months. Patient has very good partial response to crizotinib and had some side effects of crizotinib like nausea, vomiting, diarrhea, fatigue, asthenia and anorexia, asymptomatic transaminitis in the first 2 to 3 weeks of therapy and managed symptomatically. But after 9 months, he developed sudden onset left sided vision loss. On fundoscopic examination he was found to have "cherry red spot" and fundus flourescein angiography revealed central retinal artery occlusion (CRAO). After 15 days of vision loss patient developed pleural effusion, and pleural fluid cytology was positive for malignant cells. Visual symptoms are very well known in the literature as side effects of crizotinib, but CRAO is not yet been documented. As this patient is not having any prothrombotic state like diabetes, hypertension, atherosclerosis, hyperhomocysteinemia or any genetic disorders except malignancy. Hypercoagulability disorders are known to be commonly associated with a variety of cancer types including lung cancer. This appears to be a sign of early crizotinib resistance in this patient because there was no history of prior hypercoagulable state. To the best of our knowledge this is the first case report in the world literature, as CRAO presenting as a sign of crizotinib resistance in an adenocarcinoma of lung patient who was on crizotinib.